Egypt and the Millennium Development Goals : Egypt and the Millennium Development Goals - El-Saharty, Sameh; Richardson, Gail; Chase, Susan (World Bank, Washington, DC, 2013)
There are challenges that hinder progress toward the Millennium Development Goals(MDGs), targets in Egypt. These challenges include the pervasive differentials and gaps in the delivery, availability, and quality of publicly financed services and programs, the gender gaps; the fragmented legal system; and the lack of opportunity for civil society to participate in the development process. The report outlines a number of strategies to accelerate achievement of the MDGs in Egypt, including: 1) strengthening government stewardship and regulation, 2) encouraging community participation, 3) improving targeting of publicly financed services, 4) enhancing knowledge and awareness and promoting healthy behaviors, and 5) adopting a multisectoral framework. As 2015 approaches, there will be even greater attention given to the MDGs. The extent to which they are achieved will provide a benchmark for assessing how effective governments and the development community are at supporting human development. The momentum for achieving the MDGs in Egypt needs to be sustained to demonstrate that it has the systems, resources, and structures in place to improve the lives of its people. It is equally important that the focus on achieving the MDGs is not at the expense of programs and priority areas not directly linked to the MDGs.